ADRENERGIC INNERVATION OF LYMPHATIC NODES FROM VARIOUS BODY REGIONS IN YOUNG AND MATURE ANIMALS - Demchenko, G. A.; Akhmetbayeva, N. A. (Academic Journal of Physical and Chemical Sciences, 2018)
Adrenergic innervation in the tissues of cervical, mesenteric and popliteal lymph nodes in rats of different age groups (2-45 days and 10-11 months) was studied using the specific fluorescencemicroscopic method of visualization of catecholamines. Adrenergic innervation in lymph nodes of rats is present from the first days of life and in the process of postnatal ontogenesis it tends to develop and gradually become more complex and is fully formed by the 20th-30th day from birth.